Antiplatelet therapy in carotid artery stenting and carotid endarterectomy in the asymptomatic carotid surgery trial-2 - Huibers, A; Halliday, A; Bulbulia, R; Coppi, G; De Borst, G (Elsevier, 2015)
Objective Strokes are infrequent but potentially serious complications following carotid intervention, but antiplatelet therapy can reduce these risks. There are currently no specific guidelines on dose or duration of periprocedural antiplatelet treatment for patients undergoing carotid intervention. Within the ongoing Asymptomatic Carotid Surgery Trial-2 (ACST-2), this study aimed at assessing the current use of antiplatelet therapy before, during, and after CEA and CAS in patients with asymptomatic carotid stenosis. Methods Questionnaires were sent to ACST-2 collaborators seeking information about the use of antiplatelet therapy during the pre-, peri-, and post-operative periods in patients undergoing carotid intervention at 77 participating sites and also whether sites tested for antiplatelet therapy resistance. Results The response rate was 68/77 (88%). For CAS, 82% of sites used dual antiplatelet therapy (DAPT) preoperatively and 86% post-operatively with a mean post-procedural duration of 3 months (range 1e12), while 9% continued DAPT life-long. For CEA only 31% used DAPT pre-operatively, 24% post-operatively with a mean postprocedural duration of 3 months (range 1e5), while 10% continued DAPT life-long. For those prescribing postprocedural mono antiplatelet (MAPT) therapy (76%), aspirin was more commonly prescribed (59%) than clopidogrel (6%) and 11% of centres did not show a preference for either aspirin or clopidogrel. Eleven centres (16%) tested for antiplatelet therapy resistance. Conclusion There appears to be broad agreement on the use of antiplatelet therapy in ACST-2 patients undergoing carotid artery stenting and surgery. Although evidence to help guide the duration of peri-procedural antiplatelet therapy is limited, long-term treatment with DAPT appears similar between both treatment arms.